2018
DOI: 10.1186/s12902-018-0266-y
|View full text |Cite
|
Sign up to set email alerts
|

Reintroducing testosterone in the db/db mouse partially restores normal glucose metabolism and insulin resistance in a leptin-independent manner

Abstract: BackgroundTestosterone signals through the androgen receptor (AR) and AR knockout mice develop obesity, suggesting a functional association between AR and leptin signaling. Furthermore, physiological blood concentrations of testosterone have been found to inhibit the development of arteriosclerosis, obesity and diabetes. However, these findings have not been verified by testosterone replacement in animal models and whether or not testosterone acts directly by activating AR to enhance leptin signaling, or indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…As shown in Figure 5 H , castration resulted in rising trend of glucose intolerance, but without a statistical significance. Previous studies also reported that the castration-induced testosterone deficiency results in an increase in fasting blood glucose levels, and reintroducing testosterone partly rescues normal glucose metabolism ( 22 , 23 ). These results demonstrated that the effect of physiological testosterone deficiency on metabolic disorders partly provides a basis for explaining the phenotype of KO mice.…”
Section: Resultsmentioning
confidence: 85%
“…As shown in Figure 5 H , castration resulted in rising trend of glucose intolerance, but without a statistical significance. Previous studies also reported that the castration-induced testosterone deficiency results in an increase in fasting blood glucose levels, and reintroducing testosterone partly rescues normal glucose metabolism ( 22 , 23 ). These results demonstrated that the effect of physiological testosterone deficiency on metabolic disorders partly provides a basis for explaining the phenotype of KO mice.…”
Section: Resultsmentioning
confidence: 85%
“…Testosterone is a critical hormone in regulation of spermatogenesis (Walker, 2011). There is strong evidence of the negative effect of obesity on testosterone level (Craig et al, 2017; Yabiku et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which obesity causes a decline in reproductive capacity are complex, involving endocrine disorders, inherited, physical, or chemical factors (Alves et al, 2016; Craig, Jenkins, Carrell, & Hotaling, 2017; Hayden, Flannigan, & Schlegel, 2018; Sifakis, Androutsopoulos, Tsatsakis, & Spandidos, 2017). Studies have shown that testosterone is reduced in obese men and animal models, which affects spermatogenesis (Craig et al, 2017; Yabiku, Nakamoto, & Tokushige, 2018). In addition, metabolic status is critical to controlling the energy requirements of the reproductive system, and metabolic disorders caused by obesity are detrimental to reproductive function (Dimopoulou, Goulis, Corona, & Maggi, 2018; Rato et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There is an interesting paradox that, in men, testosterone deficiency increases visceral fat content and insulin resistance; while in women, high androgen levels increase insulin resistance and visceral fat [30] . At the animal model, the testosterone levels of db/db mice were lower than that of the wild type mice, and exogenous testosterone replacement alleviated fatty liver of db/db mice [31] . Estrogen, another sex hormone, is one of the protective factors of NAFLD by suppressing lipid accumulation, inflammation and fibrosis [32] .…”
Section: Trial (Adopt) and Rosiglitazone Evaluated For Cardiovascularmentioning
confidence: 92%